"There’s no cure for the Internet" - Surveillance, Spectatorship, and Sanctuary in Black Mirror - Novák, Zsófia (FOCUS: Papers in English Literary and Cultural Studies, 2020)
The British-American anthology series Black Mirror (2011-2019) constructs delicately balanced worlds that are “just realistic enough to get under the viewer’s skin, yet just extreme enough to grab attention and not let go until [the] bleak resolution” (33). The episodes that I will examine here may be read as examples of surveillance capitalism’s modus operandi. “Hated in the Nation” and “Fifteen Million Merits” present over-technologized societies characterized by a complete lack of privacy, eliminating both sanctuary and exit—which, as Zuboff also contends, is closely correlated with the individual’s lack of agency in- or outside the (social) hive (444). Although the selected episodes are characterized by substantial differences in tone, setting, plot, and aesthetic and psychological strategies, surveillance and spectatorship— complicating boundaries between externality and internality—have central functions in both. Concerned both with the characters’ experience and with the audience’s position(ality) and identification processes in the act of viewing, this essay analyses the mechanics of the filmic text in the episodes, looking at how it problematizes the central issues of spectatorship, surveillance, and (the lack of) sanctuary.